Psychometric characteristics of the Shalev Coping Effectiveness Scale Plus (SCES+) assessed in a sample of Ukrainians experiencing grief in the context of the ongoing war - Frankova , Iryna; But, Tetiana; Zelenko, Yelyzaveta; Leshchuk, Iryna; Skrynnyk, Olga; Khaustova, Olena; Chaban, Oleg (Psychosomatic Medicine and General Practice, 2025)
In conditions of ongoing war, the population faces cumulative stress: losses, forced changes in life circumstances, uncertainty, disruption of familiar social roles, etc. In this context, there is a growing need not only to assess the level of psychological distress, but also to focus on resources that support adaptation, functioning, and psychological resilience (Shalev, 2022). “Coping efficacy” is a subjective belief in one’s own ability to successfully cope with emotional and situational challenges; the term has its roots in the general theory of self-efficacy (Bandura, 1977; Bandura, 1997) and is integrated into theoretical models of stress coping (Lazarus, Folkman, 1984). Shalev’s Coping Efficacy Scale Plus (SCES+) (Shalev, 2026, in prep.) is a 6-item self-report instrument used to assess coping efficacy. The construct of coping efficacy is viewed as multidimensional and encompasses functional performance of everyday tasks, emotional regulation, interpersonal interaction, positive self-perception, the ability to focus attention on positive experiences, and adaptive decision-making in the face of change. Theoretically, the scale is consistent with models of coping self-efficacy that emphasize regulatory and functional resources rather than distress symptoms. Key words: War, grief, prolonged grief disorder, coping effectiveness, PTSD, SCES+, depression, stress, trauma